CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If one of the lines of $$my^{2}+(1-m^{2})xy-mx^{2}=0$$ is a bisector of the angle between the lines xy=0, then m= 


A
-2
loader
B
1
loader
C
2
loader
D
-1/2
loader

Solution

The correct option is B 1
The bisectors of xy = 0 ie x = 0 and y = 0, we have are
$$ x+y = 0 $$ and $$x-y = 0 $$
$$ \Rightarrow $$ Now
$$ my^{2}+(1-m^{2})xy-mx^{2}= 0$$
$$ my^{2}+1xy-m^{2}xy - mx^{2} = 0$$
$$ my (my+x)-mx(my+x) = 0$$
$$ \Rightarrow (y-mx)(my+x) = 0$$
on comparing there with x + y = 0 and x - y = 0 we have
 m = 1 

1116952_1201794_ans_9f01238f140346428ec6a3f5905f8a66.jpg

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image